Converb in Dizin - Bizualem Amlak; Girma Mengistu; Desalegn Hagos (Journal of Ethiopian Studies)
This paper describes converbs in Dizin, one of the least linguistically studied Omotic languages in the southwest part of Ethiopia. Its objective is describing and documenting converbs that appear in the language. The study follows a qualitative research approach. The data were collected using elicitation from key informants and from natural texts recorded in Maji district in 2022. The findings show that Dizin has three types of converb: general converb marked by covert suffix-∅, same-subject anterior converb –tej and different-subject anterior converb-n. The study also shows that converb clauses occur preceding the matrix clause, which accords with s-o-v languages. The study further shows that general converbs in Dizin express adverbial modification for manner, or as causal reading, and as narrative for clause-chaining, while the different-subject anterior converb and same-subject anterior converbs express events which take place one after the other. Furthermore, the study shows that some converbs become lexicalized into agent nouns and adverbs.